RENTANG KADAR ASPAL CAMPURAN BERASPAL PANAS SESUAI SPESIFIKASI BERBASIS SUPERPAVE - Nono Nono (Jurnal Jalan-Jembatan, 2010)
Conformity between the quality of hot mix asphalt construction with quality result is very difficult to achieve the plan. There are several factors that can lead to differences, among others, is the effect of lack of precision sampling, testing and manufacturing process ofthe mixture and implementation of the field. Difference of diversity of the construction is still acceptable as long as it within tolerance as specified in the specification. Tolerance in the specification reflect that the quality of the product is still acceptable because it is technically still within the range required. This paper discusses the range limit of bitumen content which still meet the requirements based Superpave specifications for various types and gradations of hot asphalt mixture, either for Laston of Lataston. Activities undertaken are included literature review, testig of materials and some types of hot mix asphalt in the laboratory and data analysis that includes a descriptive analysis to properties of material and hot mix asphalt. Analysis shows that the range limit of bitumen for hot mix asphalt-based refers to the Superpave specification, especially for the type of mixture of bitumen mixture which limits the range to meet varied requirements and more narrower (< 0.3%). As for the mixture Lataston was still quite wide, namely >= 0.4%. Since the range limit of bitumen content for Laston narrow enough, so in the process of sampling, testing and manufacturing process of the mixture and implementation of field is required precision and high accuracy. In this case associated with implementing a well-trained and well and calibrated equipment Key word : the range of bitumen content, hot mix asphalt, Superpave, tolerance, Laston and Lataston